Holistic Hermeneutics of Qur’anic Verses: Reinterpreting for Achieving Gender Equality in Contemporary Islamic Society: Hermeneutika Holistik Terhadap Ayat-Ayat Al-Qur’an: Menafsirkan Ulang untuk Mewujudkan Kesetaraan Gender dalam Masyarakat Islam Kontemporer - Muhammad Resky (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Background and Objectives: This study addresses the patriarchal bias prevalent in traditional Qur’anic exegesis, which often privileges male perspectives and neglects women’s experiences. Such interpretations can lead to gender injustices justified by certain verses. The primary objective is to explore Amina Wadud’s holistic hermeneutic approach, which aims to affirm gender equality in Qur’anic interpretation. Methodology: Employing a qualitative literature-based approach, this research integrates thematic (maudu’i) exegesis, philological analysis, and a women’s perspective. Additionally, the study draws on Hans-Georg Gadamer’s hermeneutic concepts of prejudice, fusion of horizons, and dialogue, thereby enriching a holistic framework for Qur’anic interpretation. Main Findings: The findings indicate that the Qur’an fundamentally supports gender equality. Both men and women share equal rights, obligations, and potentials—whether in worship, social roles, or broader achievements. When examined holistically, verses addressing inheritance, human origins, and gender relations emphasize justice and balance rather than legitimizing any form of gender dominance. Contributions: This research contributes by proposing a more responsive interpretive method that engages contemporary issues of gender equality. The holistic hermeneutic approach encourages re-examining verses often misunderstood in traditional commentary. Consequently, it provides a valuable resource for Islamic education, social policy, and women’s empowerment initiatives. Conclusion: This study concludes that the Qur’an does not endorse patriarchy or matriarchy but rather underscores justice and equality. While the findings remain mostly theoretical, this approach opens avenues for further research on policy implementation and inclusive, gender-just education systems.